Optimizing Contextual Features for Instagram Engagement Prediction using Long Short-Term Memory (LSTM) - Aswad, Hazrul; Mulyana, Dadang Iskandar; Kastum, Kastum (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Instagram has become an important communication medium for academic institutions, enabling the dissemination of information, promotion of activities, and engagement with the campus community. At STIKOM CKI Jakarta, the official Instagram account plays a key role in academic communication, making it essential to optimize content strategies for higher audience interaction. This study analyzes 311 publicly available posts collected from July 2023 to July 2025 from the institution’s official account. Although relatively small for deep learning, the dataset provides representative patterns for the case study while highlighting the model’s capability under limited data conditions. A predictive framework based on Long Short-Term Memory (LSTM) was developed by integrating textual features from captions with contextual features such as posting time, content type, hashtag count, and interaction metrics. The aim is to accurately estimate engagement scores and provide actionable posting recommendations. The evaluation achieved an R² of 88.00%, MAE of 0.0450, and RMSE of 0.0720, indicating strong predictive performance. The contribution of this research lies in demonstrating that optimizing contextual features can significantly enhance academic social media engagement and in providing an adaptable methodology for institutions with limited historical data.